A condição espectral da ruína - Lucas Andrade Neves Dutra Cosendey (2020)
Taking as a starting point the rupture of the Fundão Dam in Mariana, Minas Gerais, in 2015, the dissertation revolves around the preservation of Bento Rodrigues district’s ruins. Betting on the inherent potential of catastrophic situations to tension and destabilize the hegemonic thinking structures, it is firstly discussed the impropriety of indiscriminate reproduction of Cesare Brandi’s axioms to further the matter. At a second moment, based on the assumption that Cesare Brandi’s interpretation regarding the ruin is strictly ontological, it is proposed a broadening of the debate towards a “hauntology”, as defined by the deconstructivist Jacques Derrida. Whereas for Brandi the ruin no longer inhabits the architectural space, the gradual reoccupation of the ruined complex by the affected community proves to be impossible the reading of these spaces as non- places. The “hauntology” would then be a thinking on spectrums: non-corporeal figures that exist in the space of the undecidable, between what is seen and what is not; that which is neither intelligible nor sensitive nor visible nor invisible. Supported by the spectral condition’s reading, a discussion is conducted regarding the conservation and restoration’s theory and practice in post-disaster situations.